Is Native Advertisement Hybrid of Literary Text? - Tkalec, Gordana (Advances in Social Sciences Research Journal, 2025)
Native advertising is most often defined as a hybrid form that merges journalism and advertising, but this paper explores the thesis that it may also be considered a hybrid of literature. By examining the similarities between native content and literary texts — particularly their fictional basis, appellative function, objectivity or subjectivity, language and writing style, form, authorship, reader involvement, ethics and public interest — this study shows that native advertising shares several core elements with literature. While it lacks artistic intent, native advertising blurs boundaries between genres and uses literary writing and narrative techniques to enhance its persuasive effect. Through a review of recent literature and selected examples of native advertising in lifestyle media, this study demonstrates that native advertising is a hybrid of literature. It presents fictional events, uses literary descriptions and artistic style, occasionally adopts the structure of a short story, is subjective, conveys impressions and emotions, and employs narration. Unlike news articles, it does not report on real events nor answer fundamental journalistic questions, thus distancing itself significantly from journalistic form. As audiences shift from literary to digital media consumption, native advertising may be evolving into a modern, commercially driven replacement for fiction.